The Collector of Dying Breaths : a Novel of Suspense - Rose, M. J. 1953- (Thorndike, Maine : Center Point Large Print, 2014)
"This gothic tale zigzags from the violent days of Catherine de Medici's court to twenty-first-century France. Set in the forest of Fontainebleau, crisscrossing the lines between the past and the present, this mesmerizing tale of passion and obsession illuminates the true path to immortality: the legacies we leave behind. "--
Keywords: Immortality -- Fiction; Large type books; Romantic suspense fiction